2017
DOI: 10.1016/j.ultrasmedbio.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Angle Independence of Electromechanical Wave Imaging for the Measurement of Electromechanical Activation during Sinus Rhythm in Healthy Humans

Abstract: Electromechanical Wave Imaging (EWI) is an ultrasound-based technique that can non-invasively map the transmural electromechanical activation in all four cardiac chambers in vivo. The objective of this study was to demonstrate the reproducibility and angle independence of EWI for the assessment of electromechanical activation during normal sinus rhythm (NSR) in healthy humans. Acquisitions were performed transthoracically at 2000 frames/s on seven healthy human hearts in parasternal long-axis, apical four- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…ME estimates radial strain by first estimating the displacement in the axial and lateral directions. At sufficiently high motion estimation rates, accurate axial displacement estimation may be achieved; in previous publications, our group has shown that a single diverging wave sequence at 2000 Hz can image small incremental axial strains ( ε < 0.025%) associated with the electromechanical coupling in the in vivo myocardium with high reproducibility [40].…”
Section: Discussionmentioning
confidence: 99%
“…ME estimates radial strain by first estimating the displacement in the axial and lateral directions. At sufficiently high motion estimation rates, accurate axial displacement estimation may be achieved; in previous publications, our group has shown that a single diverging wave sequence at 2000 Hz can image small incremental axial strains ( ε < 0.025%) associated with the electromechanical coupling in the in vivo myocardium with high reproducibility [40].…”
Section: Discussionmentioning
confidence: 99%
“…The automation aspect also reduces the operator dependence: the 3‐D volumes calculated by two different operators are highly similar and the important points are detected at positions separated by only a few millimeters (Table ). The reproducibility of the EWI technique itself (i.e., in 2‐D) has been assessed in a separate study: the variation in activation times between two consecutive acquisition was found between 0.02 and 25.31%, with an average variation of 6.19% . Additionally, it is worth noting that the pseudo‐3D map is merely an image, while the 3‐D map is a 3‐D set of data on which calculation can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The reproducibility of the EWI technique itself (i.e., in 2-D) has been assessed in a separate study: the variation in activation times between two consecutive acquisition was found between 0.02 and 25.31%, with an average variation of 6.19%. 19 Additionally, it is worth noting that the pseudo-3D map is merely an image, while the 3-D map is a 3-D set of data on which calculation can be performed. For instance, the average of the activation times through the lateral wall of the left ventricle can be calculated in 3-D and compared to the average of the activation times in the septal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical feasibility and application of several echocardiographic techniques for measuring mechanical properties such as myocardial stiffness are currently being investigated (Correia et al, 2016;Hollender et al, 2017;Melki et al, 2017;Strachinaru et al, 2017;Pislaru et al, 2014;Vos et al, 2017;Bunting et al, 2017b,a;Villemain et al, 2018). Offline post processing of the radio frequency (RF) data is commonly used for improving the image quality of the reconstructed ultrasound sequences and improve tracking accuracy of optical flow methods (Poree et al, 2016;Joos et al, 2018;Song et al, 2013;Grondin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The segmented deformation images are normally presented superimposed on a low frame rate ultrasound detected B-mode images (Luo and Konofagou, 2010;Konofagou et al, 2010;Provost et al, 2010Provost et al, , 2015Bunting et al, 2017a;Melki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%